Bone metastases in prostate cancer – Gallium-68–labeled prostate-specific membrane antigen or Fluorine 18 sodium fluoride PET/computed tomography – the better tracer?. Issue 12 (19th October 2022) - Agrawal, Archi; Natarajan, Aravintho; Mithun, Sneha; Bakshi, Ganesh; Joshi, Amit; Murthy, Vedang; Menon, Santosh; Purandare, Nilendu; Shah, Sneha; Puranik, Ameya; Choudhury, Sayak; Prakash, Gagan; et al.
Abstract : Objective: The objective was to assess the roles of 68 Ga-PSMA PET/CT and 18 F-NaF PET/CT in evaluation of skeletal metastatic lesions in prostate cancer. Methods: Two hundred consecutive prostate cancer patients who had undergone 68 Ga-PSMA PET/CT and 18 F-NaF PET/CT at baseline evaluation ( n = 80) and following suspected recurrence or disease progression (restaging) ( n = 120) were analyzed retrospectively. Results: PSMA and NAF scans were positive for skeletal metastatic lesions in 67% (134 patients) and negative in 33% (66 patients). The scans were concordant in 80% (160 patients: 66 negative and 94 positive) and discordant in 20% (40 patients). Among 40 discordant results, 14 were baseline and 26 were restaging studies. PSMA detected more number of lesions in 11 (nine baseline and two restaging). These were true positive marrow or lytic metastatic lesions. NaF revealed more number of lesions in 29 (5 initial and 24 restaging). These were false positive on follow-up imaging. No statistical difference ( P value = 0.7 by McNemar test) between the two scans for identifying absence or presence of at least one skeletal lesion was noted at baseline staging. Conclusion: Though, both 18 F-NaF and 68 Ga-PSMA are excellent tracers for evaluation of skeletal metastases in prostate cancer, there is a distinct advantage of 68 Ga-PSMA PET/CT due to detection of additional skeletal lesions and absence of false positive lesions. In addition, absence of PSMA avidity in healed metastases in the restaging setting opens up new avenue for assessment of response of skeletal metastases.